Cryptanalysis and Improvement of an Image Encryption Scheme Using Fourier Series. Issue 4 (December 2017) - Ahmad, Musheer; Doja, M.; Beg, M.
Abstract This paper proposes cryptanalysis of an image encryption scheme reported in (Khan, J Vib Control 21(16):3450–3455, 2015). The encryption scheme synthesized nonlinear substitution-box using Fourier series to accomplish encryption of color images. Security investigation unveils that the scheme has inherent flaws which can be exploited by an attacker to reveal the plain-image information. We show that the encryption scheme is breakable under chosen-plaintext attack without owning secret key. The simulation analyses bring to notice that Khan's scheme is insecure for encryption of images during secure communication. Besides, an improved image encryption scheme is proposed which is backed up by better statistical results and performance.